Child perspectives on growing up with gender-based intimate partner violence at home - Miranda, Jenniffer K.; Rojas, Carolina; Crockett, Marcelo A.; Azócar, Estrella (Anales de Psicología / Annals of Psychology, 2021)
Growing up in the context of gender-based intimate partner violence (IPV) has been associated with mental health problems in children yet little is known about IPV effects on children from their own point of view. The aim of this research was to understand the psychological impact associated with living in an environment with IPV, from the perspective of children. Semi-structured interviews were conducted with 3 boys and 5 girls, between 8 and 12 years old, who were attending psychosocial programs specialized in maltreatment and experimented different forms of chronic IPV at home. The interviews were analyzed using narrative analysis. The results show that growing up in an environment with IPV has a psychological impact on children’s emotional wellbeing and family relationships, and in some cases on their self-concept. We conclude that IPV experiences had a profound impact on the participants’ wellbeing, affecting various areas of the children’s lives. The results highlight the importance of understanding the effects of IPV from the children’s perspective, in order to develop clinical interventions in accordance with their needs.